2019
DOI: 10.1186/s42269-019-0064-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inoculum density of Stromatinia cepivora on the amount of white rot reduced by Trichoderma species in garlic

Abstract: Background: White rot, a garlic disease caused by the soil-borne fungus Stromatinia cepivora (Berk.) Whetzel, is a serious problem of garlic productions in Egypt. This study examines the potential of controlling the disease biologically by using three Trichoderma species, i.e., Trichoderma harzianum, Trichoderma koningii, and Trichoderma virens employed either alone or in combination. Results:In in vitro assays, three Trichoderma species, i.e., Trichoderma harzianum, Trichoderma koningii, and Trichoderma viren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Culture filtrates significantly boosted onion yields compared to the non-amended control in the two field trials. These results are in concordance with the pervious findings of Davis et al (2007) and Elshahawy et al (2019b). This was also supported by Harman et al (2004) who found that after colonization of bioagent, Trichoderma spp.…”
Section: Field Experimentssupporting
confidence: 91%
See 1 more Smart Citation
“…Culture filtrates significantly boosted onion yields compared to the non-amended control in the two field trials. These results are in concordance with the pervious findings of Davis et al (2007) and Elshahawy et al (2019b). This was also supported by Harman et al (2004) who found that after colonization of bioagent, Trichoderma spp.…”
Section: Field Experimentssupporting
confidence: 91%
“…Hence, growers still depending on chemical control to eradicate the pathogen (Fullerton and Stewart, 1991;Fullerton, et al, 1995;Melero-Vara, et al, 2000). Different previous safety strategies have been applied for controlling white rot including biological and physical measurements such as soil fumigation (Entwistle, 1990), soil solarization (Melero-Vara, et al, 2000), the compost of Allium crops waste (Elshahawy et al, 2019a), crop rotation with non-Allium crops (Banks and Edgington, 1989), plant extracts (Montes-Belmont and Prados-Ligero, 2006), biological control agents and /or bioagents culture filtrates (Clarkson et al, 2006;Dilbo et al, 2015;Elshahawy et al, 2017 a,b;Elshahawy et al, 2018 a,b andElshahawy et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…The number of resistant cultivars to root-knot nematodes is limited and, in Brazil, all commercial cultivars of garlic and onion are susceptible to S. cepivora (Lourenço Júnior et al, 2018). Solarization, biofumigation, and the application of biocontrol agents may be valuable options for the management of nematodes and S. cepivora, especially when used in an integrated approach (Fuga et al, 2012;Elshahawy, Saied, Abd-El-Kareem, & Morsy, 2019;Forghani & Hajihassani, 2020).…”
Section: Introductionmentioning
confidence: 99%